DISEKSI ARTERI KAROTIS INTERNAL POSTPARTUM - Jimmy Jimmy; Ashari Bahar; Andi Kurnia Bintang; Muhammad Iqbal Basri (PERDOSNI, 2018)
POSTPARTUM INTERNAL CAROTID ARTERY DISSECTIONABSTRACTInternal carotid artery dissection is the most common cervicocephalic artery dissection. Postpartum cervicocephalic artery dissection is a rare cause of stroke in young adults. We report the case of a 27-year-old female presented to the emergency department with left hemiplegia occurred suddenly 4 days prior to admission when she was breastfeeding her5-month-old baby in the afternoon, preceded by a right headache. She has a history of migraine and experienced repeated headaches with increased pain intensity after vaginal delivery to this baby. An early brain CT scan disclosed the presence of subacute massive cerebral infarction in the distribution of proximal right middle cerebral artery territory. A carotid doppler showed absence of flow velocity and tapering luminal narrowing in the right internal carotid artery. The diagnosis was confirmed using standard digital subtraction angiography (DSA) which showed a “flame sign” of the proximal right internal carotid artery with collateral circulation from anterior communicating artery and right posterior cerebral artery to right middle cerebral artery vascularization. She was treated with the combination of acetylsalicylic acid-clopidogrel and simvastatin. A repeated brain CT scan showed improvement compared to the early brain CT scan. She showed improvement of headache and motor function.Keywords: Cervicocephalic artery dissection, DSA, migraine, postpartum, stroke in young adultsABSTRAKDiseksi arteri karotis internal merupakan kejadian tersering dari diseksi arteri servikosefalik. Diseksi arteri servikosefalik postpartum merupakan suatu penyebab stroke yang jarang pada usia muda. Dilaporkan kasus seorang perempuan 27 tahun dibawa ke unit gawat darurat dengan kelemahan tubuh sisi kiri secara tiba-tiba 4 hari sebelum masuk RS. Saat itu pasien sedang menyusui bayinya, didahului nyeri kepala sisi kanan. Pasien memiliki riwayat migren dan merasakan nyeri kepala berulang yang bertambah berat setelah melahirkan bayinya tersebut. CT scan kepala awal memperlihatkan adanya infark serebral masif subakut sesuai distribusi daerah proksimal arteri serebral media. Doppler karotis menunjukkan hilangnya kecepatan aliran dan penyempitan lumen bertahap di arteri karotis internal kanan. Diagnosis dikonfirmasi dari gambaran digital subtraction angiography (DSA) berupa flame sign di arteri karotis internal kanan bagian proksimal dengan sirkulasi kolateral dari arteri komunikans anterior dan arteri serebral posterior kanan ke vaskularisasi arteri serebral media kanan. Pasien diterapi dengan kombinasi asam asetilsalisilat-klopidogrel dan simvastatin. CT scan kepala kontrol memperlihatkan perbaikan dibandingkan dengan CT scan kepala awal. Pasien menunjukkan perbaikan nyeri kepala dan kekuatan motorik.Kata kunci: Diseksi arteri servikosefalik, DSA, migren, postpartum, stroke usia muda